PEMBELAJARAN NIRMANA PADA MATA PELAJARAN SENI BUDAYA DI KELAS VII A SMPN 2 PADANG PANJANG - Muhammad Irsyad; Chairul Haq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the limited implementation of visual art learning at SMP Negeri 2 Padang Panjang, where the arts and culture teacher has a background in traditional music, resulting in visual art learning that has not been carried out optimally. This research focuses on the process and results of nirmana learning in the Arts and Culture subject in class VII A of SMP Negeri 2 Padang Panjang. The method used is descriptive qualitative with the research subjects being all 31 students of class VII A. Data collection techniques include literature study, observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and conclusion drawing. The results show that nirmana learning took place over eight meetings using the Project Based Learning (PjBL) model based on constructivist learning theory, starting from the introduction of basic concepts, two-dimensional work, sketch design, assembly, gradation coloring, to the combining and lamp installation on functional three-dimensional nirmana works. Student learning outcomes showed a class average score of 87,44, with sixteen students in the high category, ten in the medium category, and five in the low category.